My cousin vinny - Launer, Dale; Schiff, Paul; Lynn, Jonathan; Twentieth Century-Fox Film Corporation; Twentieth Century Fox Home Entertainment, Inc. (Beverly Hills, CA : Twentieth Century Fox Home Entertainment, 1992)
Two carefree pals travelling through Alabama are mistakenly arrested and charged with murder. They are defended by one of their cousins (Vinny), a former auto mechanic of Brooklyn who just passed his bar exam after his sixth try. Vinny's never been in court and the case quickly turns into a hysterical escapade.
Director of photography, Peter Deming ; editor, Tony Lombardo ; music, Randy Edelman
Cast : Joe Pesci, Marisa Tomei, Ralph Macchio, Mitchell Whitfield, Fred Gwynne.
Keywords: Trials (Murder) -- Alabama -- Drama; Lawyers -- New York (State) -- Drama